A novel design and control method for improved LCL filter three-level inverter to suppress common mode resonant current and leakage current. Issue 1 (1st November 2022) - Chen, Weilun; Zhang, Guorong; He, Haiyang; Wu, Zhizhen
Abstract : The method of connecting the common point of the LCL filter capacitor of the three-level grid-connected inverter to the midpoint of the DC side can effectively suppress the leakage current between the DC side photovoltaic panel and the power grid. However, the improved MLCL inverter is easy to generate common mode resonance, which results in excessively increasing the midline current and affecting the efficiency and stability of the system. Aiming at the common mode resonance problem of MLCL three-level inverter, this paper expounds the generation of common mode resonance current and large neutral current by establishing the mathematical model of the improved MLCL filter. After analyzing the restraining effect and limitation of traditional passive damping control scheme on common mode resonance, a novel filtering structure is proposed in this paper, which is combined with PI+ PR double closed-loop control scheme to solve the above problems. Simulation results verify the validity of the analysis on common mode resonance and neutral current, and the effectiveness of the scheme in suppressing common mode resonance current, midline current and leakage current is also confirmed.